Relevansi Pemeriksaan Calon Tersangka sebelum Penetapan Tersangka - Erdianto Effendi (Undang: Jurnal Hukum, 2020)
In Indonesian criminal procedure law, there is no requirement for an investigator to first conduct an examination of a potential suspect until the determination as a suspect. The determination of a suspect is deemed sufficiently reasonable if it is based on examination of evidence, ranging from witness testimony, expert testimony, document and other evidence. After the Decision of the Constitutional Court Number 21/PUU-XII/2014, there were differences in interpretation and debate regarding the examination of the potential suspect, because this examination was mentioned in the consideration of the decision as a necessity but not part of the verdict. In this article, it is revealed that the designation of a person as a suspect is part of forced efforts and is almost equivalent to the designation of a person as a convicted person due to the similarities in the various restrictions and deprivation of rights that can be applied as a result of the two determinations, for example in detention. The shift in the meaning of the determination of a suspect as part of this forced effort encourages that citizens’ rights be protected not only when a person is a suspect, but also before becoming a suspect. Thus, the rights inherent in a suspects also needs to be given to those who will be designated as suspects, also called as potential suspects. Abstrak Dalam hukum acara pidana Indonesia, tidak ada keharusan bagi penyidik untuk terlebih dahulu melakukan pemeriksaan calon tersangka sehingga sampai pada penetapannya sebagai tersangka. Penetapan tersangka dipandang telah cukup beralasan apabila didasarkan pada pemeriksaan alat bukti, mulai dari keterangan saksi, keterangan ahli, surat, dan bukti lainnya. Pasca Putusan Mahkamah Konstitusi Nomor 21/PUU-XII/2014, terjadi perbedaan penafsiran dan perdebatan tentang pemeriksaan calon tersangka ini, disebabkan pemeriksaan ini disebut dalam bagian pertimbangan putusan sebagai suatu keharusan namun tidak menjadi bagian amar putusan. Dalam artikel ini ditunjukkan, penetapan seseorang sebagai tersangka merupakan bagian dari upaya paksa dan bahkan hampir setara dengan penetapan seseorang sebagai terpidana, disebabkan kesamaan berbagai pembatasan dan perampasan hak yang dapat diterapkan akibat dari dua penetapan tersebut, misalnya dalam penahanan. Perubahan pemaknaan penetapan tersangka sebagai bagian dari upaya paksa ini mendorong agar hak-hak warga negara telah harus dilindungi tidak saja ketika seseorang sudah berstatus tersangka, tetapi juga pada saat sebelum menjadi tersangka. Dengan demikian, hak-hak yang melekat dalam diri tersangka juga perlu diberikan kepada mereka yang akan ditetapkan sebagai tersangka, atau disebut calon tersangka.